THE RELATIONSHIP BETWEEN RENEWABLE ENERGY CONSUMPTION, TRADE OPENNESS AND ECONOMIC GROWTH: THE CASE OF BOSNIA AND HERZEGOVINA - Yilmaz Onur Ari (Economic Review)
The paper examines the renewable energy con-sumption-trade openness-economic growth ne-xus for Bosnia and Herzegovina using annual time series data covering the period of 1994-2015. The variables in the analysis were checked using Augmented Dickey Fuller test statistics. The results obtained indicated that economic growth became stationary at level while rene-wable energy consumption and trade openness variables became stationary at first difference. According to Todo-Yamamoto Causality Test results, there is a unidirectional causality from renewable energy consumption to economic growth at 5 % in the long run. This finding is in line with the growth theory which remarks unidirectional/one-way causality from renewa-ble energy consumption to economic growth. In this case, renewable energy dependent conser-vation policy may have prohibitive effect on economic growth. The study also concluded that there is no association between trade openness and economic growth. Thus, the finding su-pports the neo-classical growth theory. Besides, there is a causality from renewable energy co-nsumption to trade openness, so the conser-vation policies will affect the trade and trade liberalization policies designed to promote eco-nomic growth.